Analisis Komitmen Kinerja Karyawan Klinik Pratama Asshofwan - Lia Awalia; Uus Mohammad Darul Fadli (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2024)
Human resources are a central factor in managing an employee. However, the sophistication of technology used without human support as the implementer of operational activities will not be able to produce outputs in accordance with the expected level of efficiency. Previous or relevant research is fundamental in a research or scientific article. This study aims to analyze: 1) The effect of work commitment applied to the clinic, 2) the effect of work commitment on the performance of clinic employees. Whether or not there is a commitment in employee performance, because it can affect the quality of work and service. The design of this research is qualitative research and is an interview research. The research population of all Klikik Pratama Asshofwan employees and a sample of 5 respondents with interview analysis. The results of the study showed: 1) The work commitment implemented by the clinic leader is good enough in improving employee performance, 2) Work commitment affects employee performance, with proper and good implementation, 3) Work commitment is significant in relation to the responsibility of an employee in completing a job.